Periarteriolar Glioblastoma Stem Cell Niches Express Bone Marrow Hematopoietic Stem Cell Niche Proteins. (March 2018) - Hira, Vashendriya V.V.; Wormer, Jill R.; Kakar, Hala; Breznik, Barbara; van der Swaan, Britt; Hulsbos, Renske; Tigchelaar, Wikky; Tonar, Zbynek; Khurshed, Mohammed; Molenaar, Remco J.; Van Noorden, Cornelis J.F.
In glioblastoma, a fraction of malignant cells consists of therapy-resistant glioblastoma stem cells (GSCs) residing in protective niches that recapitulate hematopoietic stem cell (HSC) niches in bone marrow. We have previously shown that HSC niche proteins stromal cell–derived factor-1α (SDF-1α), C-X-C chemokine receptor type 4 (CXCR4), osteopontin (OPN), and cathepsin K (CatK) are expressed in hypoxic GSC niches around arterioles in five human glioblastoma samples. In HSC niches, HSCs are retained by binding of SDF-1α and OPN to their receptors CXCR4 and CD44, respectively. Protease CatK cleaves SDF-1α to release HSCs out of niches. The aim of the present study was to reproduce the immunohistochemical localization of these GSC markers in 16 human glioblastoma samples with the addition of three novel markers. Furthermore, we assessed the type of blood vessels associated with GSC niches. In total, we found seven GSC niches containing CD133-positive and nestin-positive GSCs as a single-cell layer exclusively around the tunica adventitia of 2% of the CD31-positive and SMA-positive arterioles and not around capillaries and venules. Niches expressed SDF-1α, CXCR4, CatK, OPN, CD44, hypoxia-inducible factor-1α, and vascular endothelial growth factor. In conclusion, we show that GSC niches are present around arterioles and express bone marrow HSC niche proteins.